Occupational Behaviors and Quality of Life: A Comparison Study of Individuals Who Self-identify as Adult Children of Alcoholics and Non-Adult Children of Alcoholics - Vaught, Emily L. (International Journal of Psychosocial Rehabilitation, 2014)
An estimated 43% of adults in the U.S. come from families with a history of alcoholism. They are described as victims of an alcoholic family environment, including polytraumatic experiences which may interfere with normal development and interpersonal functioning. Long-term effects of alcoholism within the family structure are especially reflective in the lives of adult children of alcoholics (ACOAs). This study uses a quantitative, non-experimental survey design to acknowledge and understand whether a relationship exists between occupational behaviors and quality of life, as well as the implications of growing up with an alcoholic parent and/or guardian. Survey instruments used include the Adapted Flanagan Quality of Life Scale (QOLS) and Occupational Behaviors Satisfaction Checklist (OBSC). Results were indicative of an existing relationship between overall quality of life and satisfaction with occupational engage- ment with differences noted between ACOAs and non-ACOAs. Gaining a better understanding of the relationship between occupational behaviors and quality of life affords occupational therapists and other healthcare providers the ability to supplement mental health treat- ment to achieve improved quality of life and to establish skills which will foster rich and meaningful occupational engagement.